The quality of university training in the field of Science and Techniques of Physical and Sports Activities according to the point of view of students - Ababsa, Youcef; Messahli, Seghir (sports creativity, 2023)
According to the point of view of the master's students of the Department of Science and Technology of Physical Activities and Sports at the University of Setif 2, the study aimed to identify the level of quality of university training, as it was applied to a sample of 84 students who were randomly selected. The university training was designed by the researcher, after presenting it to arbitration and making sure its psychometric characteristics, and after statistical analysis of the data, the results showed that the level of quality of university training (quality of university training programs, quality of teaching efficiency of university professors) is high according to master’s students view point, and that the level of quality of pedagogical means and facilities Sports average too.